Transformation of Used Clothes into Flower Pots in Dongkelan Hamlet, Bantul - Nugroho, Joko Purwanto; Andika; Mangku, I Ketut; Harnaji, Bimo (IJCS: International Journal of Community Service, 2023)
Used clothing is one of the sources of waste in Bantul Regency. Without proper management, this type of waste can harm the environment. One concrete example can be seen in RT1 of Dongkelan Hamlet, where the accumulation of used clothing waste occurred due to the community's lack of understanding of its environmental impact and economic potential. To address this, a comprehensive outreach program was initiated to increase community awareness and understanding. The program was divided into four stages: observation, outreach, practice, and evaluation. Before the outreach, participants showed minimal understanding of used clothing waste, with an average score of 75%, which falls into the "less" category. However, after attending the outreach, their understanding improved significantly, especially regarding the impacts and benefits of used clothing waste and how to make flower pots. Interestingly, of all the participants, 60% were interested in putting this new knowledge into practice, while the remaining 40% chose other methods, citing hassle and other reasons. In conclusion, this outreach program proved effective and is recommended to be implemented in other locations to support environmental sustainability and potential income generation.